RELATIONSHIP BETWEEN DEMOCRATIC PARENTING PATTERNS AND RELIGIOSITY WITH SELF CONTROL OF MADRASAH ALIYAH STUDENTS STATE (MAN) 1 MEDAN - Ridha Rahma Nisa Hasibuan; Hasanuddin; Yudistira Fauzy Indrawan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
Self Control of students today are often problematic in carrying out learning. Self control is certainly influenced by many factors. This study aims to analyze and determine the relationship between democratic parenting patterns and religiosity on self control. This study is included in quantitative research that is associative causal. The sample of this study was 106 students spread across SMA MAN 1 Medan. The research data were collected using a research scale that was declared valid and reliable. The data analysis technique used multiple linear regression analysis. The results of the study showed that (1)There is a relationship between democratic parenting patterns and self-controlis 4.150 > t table 1.98 and the Sig. value is 0.000, which is < significance level 0.05, then Based on the research results, it can be concludedmeans that the level of democratic parenting patterns is high and lowhaving children can increase or decrease self-control. (2)there is a relationship between religiosity and self-control.From the results of the statistical analysis, it was found that the correlation coefficient rx2y was 0.572 with p < 0.05, thus it can be concluded that the amount of religiosity received by children will be able to increase or decrease self-control. (3)There is a relationship between democratic parenting patterns and religiosity with self-control.From the results of statistical analysis, it was found that the regression coefficient value of the Democratic Parenting Pattern variable (X1) is 0.439, which is positive. This means that Democratic Parenting Pattern (X1) has a positive effect on Self Control (Y). It is known that the t statistic or t count of Democratic Parenting Pattern (X1) is 4.150> t table 1.98 and the Sig. value is 0.000, which is <0.05 significance level. Thus, it can be concluded that democratic parenting patterns and religiosity together have an effect on self control, the contribution of both in increasing children's (students') self control is 36.8% while the remaining 63.2% can be explained by other variables outside the variables proposed in the study. Democratic Parenting Pattern (X1), Religiosity (X2) are able to influence Self Control (Y) by 36.8%, the remaining 100% - 36.8% = 63.2% is explained by other variables or factors.